Vadba namiznega tenisa kot del aktivnega staranja oseb z nevrodegenerativnimi boleznimi - Paulin, Erik (Šport (Ljubljana), 2024)
Table tennis is known for its brief and fast ball exchanges. It does not require much space and is suitable for all generations, while also being a safe activity. In the general population, it is an effective activity for improving physical health and various motor skills. It also stimulates high brain activity, primarily in the sensorimotor, frontal, and visual cortices. All these characteristics have the potential to enhance health not only in general population but also in individuals with neurological conditions. The purpose of this review is to shed light on current developments in the field of therapeutic table tennis exercise for individuals with Parkinson’s disease and its preventive role against dementia as part of active aging.
Keywords: active aging; aging; aktivno staranje; exercise; namizni tenis; neurodegenerative diseases; nevrodegenerativne bolezni; sport; staranje; šport; vadba